Study of factors influencing the success of foot and mouth disease (FMD) vaccination in beef cattle in North Sumatera Province - Hutagaol, Nensy Maruana; Tafsin, Ma'ruf; Faisal, Faisal (The Faculty of Veterinary Medicine of Syiah Kuala University, 2024)
Vaccination is one of the important measures in controlling FMD in livestock. Therefore, to assess the success of FMD vaccination in livestock, it is necessary to evaluate the immune response of vaccinated animals in field conditions. This research aims to examines the effectiveness of foot and mouth disease (FMD) vaccination in North Sumatra Province and the factors influencing its success. The calculations using multiple logistic regression showed that the factors that significantly influence the effectiveness of FMD vaccination are time of vaccination, maintenance system, disinfection of cages, and farms implementing biosecurity. Based on the research that has been carried out, the advice that can be given to the North Sumatra Provincial Government is to pay attention to small-scale breeders. Because many smallholder farmers still lack knowledge, especially in implementing biosecurity.